Knowing That P without Believing That P - Myers-Schulz, Blake; Schwitzgebel, Eric (Noûs (Bloomington, Indiana), 2013)
Most epistemologists hold that knowledge entails belief. However, proponents of this claim rarely offer a positive argument in support of it. Rather, they tend to treat the view as obvious and assert that there are no convincing counterexamples. We find this strategy to be problematic. We do not find the standard view obvious, and moreover, we think there are cases in which it is intuitively plausible that a subject knows some proposition P without—or at least without determinately—believing that P. Accordingly, we present five plausible examples of knowledge without (determinate) belief, and we present empirical evidence suggesting that our intuitions about these scenarios are not atypical.